2012
DOI: 10.1111/j.1747-0285.2012.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleotide, Inhibitor, and Cation Binding Sites of P‐type II ATPases

Abstract: P-type ATPases constitute a ubiquitous superfamily of cation transport enzymes, responsible for carrying out actions of paramount importance in biology such as ion transport and expulsion of toxic ions from cells. The harmonized toggling of gates in the extra-and intracellular domains explain the phenomenon of specific cation binding in selective physiological states. A quantitative understanding of the fundamental aspects of ion transport mechanism and regulation of P-type ATPases requires detailed knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 63 publications
0
8
0
5
Order By: Relevance
“…The (Na + ,K + )-ATPase, a transport enzyme located basolaterally in epithelial cells, is a major effector of ammonia excretion in aquatic invertebrates (Weihrauch et al, 2009). This enzyme is the most prominent member of the P-type vertebrate ATPase family (Toyoshima et al, 2013;Chourasia and Sastry, 2012;Poulsen et al, 2010) and transports three Na + out of and two K + into the cell cytoplasm for each molecule of ATP hydrolyzed. Compared to the vertebrate enzyme, the structure of the crustacean gill (Na + ,K + )-ATPase is poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…The (Na + ,K + )-ATPase, a transport enzyme located basolaterally in epithelial cells, is a major effector of ammonia excretion in aquatic invertebrates (Weihrauch et al, 2009). This enzyme is the most prominent member of the P-type vertebrate ATPase family (Toyoshima et al, 2013;Chourasia and Sastry, 2012;Poulsen et al, 2010) and transports three Na + out of and two K + into the cell cytoplasm for each molecule of ATP hydrolyzed. Compared to the vertebrate enzyme, the structure of the crustacean gill (Na + ,K + )-ATPase is poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…ATP is considered to play both a catalytic and an allosteric role in the (Na + , K + )-ATPase reaction cycle (Beaugé et al, 1997; Krumscheid et al, 2004), and high and low affinity ATP- binding sites on the (Na + , K + )-ATPase are well known (Glynn, 1985; Ward and Cavieres, 1998). However, despite the plethora of crystallographic data suggesting a binding site within the (Na + , K + )-ATPase N-domain (Kanai et al, 2013; Nyblon et al, 2013; Chourasia and Sastry, 2012; Shinoda et al, 2009; Morth et al, 2007), its exact localization on the enzyme molecule remains an open question (Krumscheid et al, 2004; Morth et al, 2007). Regulatory phosphorylation by protein kinases can alter the kinetic profile of the host enzyme, e. g ., phosphorylation by PKA of liver phosphofructokinase II dramatically changes kinetic behavior in response to glucagon (Pilkis et al, 1988, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the E1·AlF4 − ·ADP·3Na + crystal structure from pig kidney (Na + , K + )-ATPase suggests that the M5 α-helix mediates coupling between the ion- and nucleotide-binding sites (Kanai et al, 2013). Crystallographic studies revealed either low- or high-affinity ATP binding sites present in the N-domain depending on conformational state (Morth et al, 2007; Shinoda et al, 2009; Chourasia and Sastry, 2012; Nyblom et al, 2013). The E1 conformation binds ATP with high affinity in the presence of Na + (Kanai et al, 2013; Nyblon et al, 2013) while the E2 conformation binds ATP with low affinity in the presence of K + (Morth et al, 2007; Shinoda et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Elas são divididas em quatro grupos bem definidos, as superfamílias das P-, F-, V-e M-ATPases (Pedersen & Amzel, 1993). As P-ATPases (Figura 2) são caracterizadas por receberem o grupo fosfato em um resíduo de aspartato presente na sequência conservada DKTGT(I/L) (Bublitz et al, 2010;Chourasia & Sastry, 2012).…”
Section: (Na + K + )-Atpaseunclassified
“…Modificado de Goodsell, 2009. As P-ATPases são classificadas em cinco diferentes famílias: I, II, III, IV e V, baseado no alinhamento de uma sequência conservada de 159 aminoácidos (Bublitz et al, 2010;Chourasia & Sastry, 2012). Dentre eles, o grupo II é o mais bem estudado e inclui a Ca 2+ -ATPase, a (Na + , K + )-ATPase e a (H + , K + )-ATPase.…”
Section: Figura 2 Estrutura Das Bombas Iônicas Pertencentes à Famíliunclassified